Late Stent Thrombosis in a Patient with Endovascular Aortic Repair for Blunt Thoracic Aortic Injury - Michael H. Chiu; Youri Kaitoukov; Amanda Roze des Ordons (Case Reports in Vascular Medicine)
Blunt thoracic aortic injury (BTAI) is associated with high mortality and morbidity. Thoracic endovascular aortic repair has become the recommended treatment modality given improved short-term results compared to open repair. We present a case of a 19-year-old male who presented with acute paralysis and multiorgan dysfunction from acute TEVAR thrombosis. Systemic thrombolysis, catheter-directed thrombolysis followed by aspiration thrombectomy, and angioplasty were initially successful in restoring perfusion. However, he developed progressive multiorgan failure related to prompt reocclusion within 48 hours. This case is the first to describe thrombolysis and angioplasty as a management strategy for acute TEVAR thrombosis. We also review the literature surrounding this uncommon complication.